Improvements in sleep, weight, and eating-disorder symptoms following off-label leptin treatment in an adolescent with chronic anorexia nervosa and insomnia: a case report - Alexander Dück; Hang Zhu; Judith Melinat; Monika Kruzer; Christoph Berger; Michael Kölch; Martin Reinhardt; Hannes Brehme; Annelie Zimmermann; Linda Frintrop; Olaf Reis (Journal of Eating Disorders, 2026)
Abstract We report off-label administration of human recombinant leptin (metreleptin) over a 12-day period in a 17-year-old female adolescent with chronic anorexia nervosa (AN) and clinically significant insomnia. Two observation windows are distinguished throughout: a short-term window between day 1 (pre) and day 12 (post) of dosing, and a longer-term window between day 12 and the two-month follow-up (d + 60), capturing both changes temporally associated with leptin administration and the course of continued weight gain after the end of dosing. Over the short-term window the clinical course comprised a modest weight gain (BMI 15.4 → 16.2 kg/m²), a marked reduction in eating-disorder cognitions and compulsive exercise, attenuation of starvation-associated motor hyperactivity, and changes in objective sleep architecture (more N3 sleep, less wake after sleep onset). In this window, broader cognitive-affective and depressive symptom dimensions remained largely unchanged, and subjective insomnia did not yet improve. Over the longer-term window the course comprised continued substantial weight gain (BMI 18.3 kg/m² at d + 60), a marked drop in subjective insomnia, partial normalisation of circadian rhythm parameters in nonparametric analysis, and a transient increase in broader cognitive-affective symptoms. As a single retrospective case observation, the findings are hypothesis-generating and cannot be disentangled from concurrent weight gain and inpatient treatment.